Mobile Learning Applications: Exploring Location Sensing Mechanisms - Challiol, Cecilia (2018)
In this paper, we present an exploration of two location sensing mechanisms, such as QR codes and beacons, used in Location-based Learning Applications which are performed inside small indoor spaces (e.g. a classroom). The exploration of QR codes was carried out through an implementation of a Location-based Learning Application which was used by students between 7 and 11 years old inside of Primary Schools. Meanwhile, for the exploration of beacons, a functional prototype was made which was systematically tested by students of Faculty of Informatics of UNLP (Argentina). We analysed those characteristics that we have been learned related to how these mechanisms behave when they are used inside small indoor spaces because, in these cases, relevant places to provide learning contents are nearest from each other. We wish to create a discussion about the exploration of these two location sensing mechanisms. We expect that this discussion helps not only to design and develop Location-based Learning Applications, but also to improve authoring tools that are using to generate this kind of applications.